Defective Proventriculus Regulates Cell Specification in the Gastric Region of Drosophila Intestine - Mehrotra, Sonam; Bansal, Priyanka; Oli, Neha; Pillai, Saraswathi Jayarajan; Galande, Sanjeev (Frontiers in Physiology, 2020)
The gastrointestinal tract in metazoans consists of diverse epithelial cells with distinct cell morphology and physiological functions. The development and homeostasis of gastrointestinal epithelia involve spatiotemporal regulation by many signaling pathways, essential to confer their region-specific function and identity. The adult Drosophila midgut and the mammalian intestine share a high degree of conservation between such signaling pathways. Due to availability of sophisticated techniques for genetic manipulation, Drosophila is an excellent model to study mechanisms of tissue homeostasis regulation in a regionally defined manner. The gastric region located in the Drosophila middle-midgut coincides with the region containing fewest number of stem cells. It is also known as the copper cell (CC) region since it is composed of specialized groups of acid-secreting CCs, along with interstitial cells and enteroendocrine cells. The generation and maintenance of these cell populations are determined by the bone morphogenic protein-like Decapentaplegic (Dpp) signaling pathway. The morphogenic gradient of the Dpp signaling activity induces differential expression of specific transcription factors labial (lab) and defective proventriculus (dve), which are required for the generation of various cell types specific to this region. In this study, we investigated the role of Dve in regulation of tissue homeostasis in the CC region. Our studies reveal that ectopic expression of dve in stem cells suppresses their self-renewal throughout the intestine. We further demonstrate that Dve is not required for generation of CCs. Higher levels of Dve can alter cell specification by inhibition of cut expression, which in turn prevents CC formation during homeostasis.